Частота виявлення антитіл до тиреопероксидази та глютаматдекарбоксилази серед хворих на цукровий діабет 1-го типу - Лихоносов, П. М.; Маньковський, Б. М. (Clinical Endocrinology and Endocrine Surgery, 2017)
The group of 282 patients diabetes mellitus type 1 which data were precised in national diabetic register were examined. The diabetes type was specified according to WHO criteria from 1999. The diagnosis was changed in 42 (14.9%) patients with diabetes mellitus type 2 that are needed insulin. In the group of patient with confirmed diabetes mellitus type 1 (n=240) anthropologic data, anamnesis data were evaluated, day insulin dose was specified, antibodies for thyroperoxidase and glutamic acid decarboxylase were evaluated with thyroid gland function. The correlation analysis depending on diabetes mellitus duration. It was determined that prevalence of diabetes mellitus type 1 is the same in men and in women. In 10 % of cases hypothyroidism was found which frequency were significantly higher in women (83% from all the hypothyroidism cases). The main cause of hypothyroidism was autoimmune thyroiditis (79% of patients with hypothyroidism had high levels of TPO antibodies). The day insulin dose in women (52 unit per day) was significantly lower than in man (62 unit per day) regardless of body weight index, age, duration of disease. The compensation was unsatisfactory (Hb1c — 9,38±3,17%). With increasing of disease duration levels of C peptide and GAD antibodies were decreasing significantly. In other hand levels of TPO antibodies, TTH, cholesterol and average day insulin dose were increasing. The prevalence of GAD antibodies in examined population was 12.9 % (15% in men and 108% in women), TPO antibodies — 34.5% (23.3% in men and 45.8% in women). In the same time antibodies for GAD and TPO were observed in 13 patients (5.4%) without differences in sex.